Resin composition

JP7639386B2Active Publication Date: 2025-03-05AJINOMOTO CO INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021023283
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-17
Publication Date
2025-03-05
Estimated Expiration
2041-02-17

AI Technical Summary

Benefits of technology

【0008】 本発明によれば、誘電正接が良好であり、ピール強度に優れ、及びデスミア処理後にクラックの発生が抑制された硬化物を得ることができる樹脂組成物;前記樹脂組成物を含む樹脂組成物層を備える樹脂シート;前記樹脂組成物の硬化物で形成された絶縁層を含むプリント配線板;並びに、前記プリント配線板を含む半導体装置;を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639386000001
    Figure 0007639386000001
  • Figure 0007639386000002
    Figure 0007639386000002
  • Figure 0007639386000003
    Figure 0007639386000003
Patent Text Reader

Abstract

To provide, e.g., a resin composition capable of forming a cured product which has a favorable dielectric loss tangent and excellent peel strength and reduces generation of cracks after desmear treatment.SOLUTION: A resin composition comprises (A) an epoxy resin represented by the general formula (1) in the figure, and (B) an active ester based curative. In the general formula (1), R represents an alkyl group.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition. The present invention further relates to a cured product of the resin composition, and a resin sheet, a printed wiring board, and a semiconductor device obtained by using the resin composition. [Background technology]

[0002] As a manufacturing technique for printed wiring boards, a manufacturing method using a build-up method in which insulating layers and conductor layers are alternately stacked is known. In the manufacturing method using the build-up method, the insulating layer is generally formed by curing a resin composition. As such a resin composition, for example, the resin composition disclosed in Patent Document 1 is known. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2019-66792 A Summary of the Invention [Problem to be solved by the invention]

[0004] A cured product formed by curing the resin composition can be used as an insulating layer of a printed wiring board of a semiconductor device. Therefore, the cured product is required to have a good dielectric tangent. In addition, it is desirable that the insulating layer formed of the cured product has excellent peel strength between the insulating layer and the plated conductor layer. Furthermore, it is desirable that the occurrence of cracks after desmearing is suppressed.

[0005] The present invention has been made in view of the above-mentioned problems, and has an object to provide: a resin composition which can give a cured product having a good dielectric tangent and excellent peel strength and in which the occurrence of cracks is suppressed after a desmear treatment; a resin sheet including a resin composition layer which includes the resin composition; a printed wiring board which includes an insulating layer formed of a cured product of the resin composition; and a semiconductor device which includes the printed wiring board. [Means for solving the problem]

[0006] As a result of intensive research into solving the above-mentioned problems, the present inventors have found that the above-mentioned problems can be solved by using (A) a specific epoxy resin and (B) an active ester curing agent, and have completed the present invention.

[0007] That is, the present invention includes the following. [1] (A) an epoxy resin represented by the following general formula (1), and (B) a resin composition comprising an active ester-based curing agent. [ka] (In the general formula (1), R represents an alkyl group.) [2] The resin composition according to [1], further comprising (C) an inorganic filler. [3] The resin composition according to [1] or [2], further comprising (D) an elastomer. [4] The resin composition according to any one of [1] to [3], further comprising (E) a high molecular weight component. [5] The resin composition according to any one of [1] to [4], further comprising (F) a curing accelerator. [6] The resin composition according to any one of [1] to [5], wherein the component (A) contains an epoxy resin represented by general formula (2). [ka] (In general formula (2), R 1 represents an alkyl group. [7] A resin sheet comprising a support and a resin composition layer provided on the support, the resin composition layer comprising the resin composition according to any one of [1] to [6]. [8] A printed wiring board comprising an insulating layer formed from a cured product of the resin composition according to any one of [1] to [6]. [9] A semiconductor device comprising the printed wiring board according to [8]. Effect of the Invention

[0008] According to the present invention, it is possible to provide a resin composition which can give a cured product having a good dielectric tangent and excellent peel strength and in which the occurrence of cracks is suppressed after a desmear treatment; a resin sheet including a resin composition layer which includes the resin composition; a printed wiring board which includes an insulating layer formed of a cured product of the resin composition; and a semiconductor device which includes the printed wiring board. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The present invention will be described below with reference to embodiments and examples. However, the present invention is not limited to the embodiments and examples shown below, and may be modified and implemented as desired without departing from the scope of the claims of the present invention and their equivalents.

[0010] [Resin composition] The resin composition of the present invention contains (A) an epoxy resin represented by the following general formula (1) and (B) an active ester-based curing agent. [ka] (In the general formula (1), R represents an alkyl group.)

[0011] In the present invention, by including component (A), it is possible to obtain a cured product having a good dielectric tangent, excellent peel strength, and suppressed crack generation after desmearing. In addition, in the present invention, it is also possible to obtain a cured product having a low coefficient of thermal expansion (CTE) and a high glass transition temperature.

[0012] The resin composition may further contain optional components such as (C) an inorganic filler, (D) an elastomer, (E) a high molecular weight component, (F) a curing accelerator, (G) an epoxy resin other than the component (A), (H) a curing agent other than the component (B), and (I) other additives, as necessary. Each component will be described below.

[0013] <(A) Epoxy resin represented by general formula (1)> The resin composition contains, as component (A), an epoxy resin (A) represented by general formula (1). [ka] (In the general formula (1), R represents an alkyl group.)

[0014] By including component (A) in the resin composition, the peel strength can be improved, the occurrence of cracks after desmearing can be suppressed, and the mechanical strength of the cured product can be improved.

[0015] The component (A) is preferably liquid at a temperature of 25°C from the viewpoint of reducing the viscosity of the resin composition.

[0016] In the general formula (1), R represents an alkyl group. The alkyl group may be linear, branched, or cyclic, and is preferably linear. The alkyl group is preferably an alkyl group having 1 to 10 carbon atoms, more preferably an alkyl group having 1 to 6 carbon atoms, and even more preferably an alkyl group having 1 to 3 carbon atoms, and is particularly preferably a methyl group from the viewpoint of obtaining the effects of the present invention significantly.

[0017] The bonding position of R in the general formula (1) is preferably the ortho position relative to the position where the benzene ring is bonded to the nitrogen atom.

[0018] The epoxy resin represented by general formula (1) preferably contains an epoxy resin represented by general formula (2). [ka] (In general formula (2), R 1 represents an alkyl group.

[0019] In general formula (2), R 1 represents an alkyl group and is the same as R in general formula (1).

[0020] As the component (A), a commercially available product can be used. Examples of commercially available products include "ELM-100H" and "ELM-100" manufactured by Sumitomo Chemical Co., Ltd. As the component (A), one type may be used alone, or two or more types may be used in combination.

[0021] The epoxy equivalent of the (A) component is preferably 50 g / eq. to 5000 g / eq., more preferably 50 g / eq. to 3000 g / eq., even more preferably 80 g / eq. to 2000 g / eq., and even more preferably 90 g / eq. to 1000 g / eq. or 90 g / eq. to 500 g / eq. When it is in this range, the crosslink density of the cured product is sufficient, and an insulating layer with small surface roughness can be obtained. The epoxy equivalent can be measured according to JIS K7236 and is the mass of a resin containing one equivalent of an epoxy group.

[0022] The molecular weight of the component (A) is preferably 100 to 5,000, more preferably 150 to 3,000, and even more preferably 250 to 1,500, from the viewpoint of achieving remarkable effects of the present invention.

[0023] From the viewpoint of obtaining the effects of the present invention significantly, the content of the (A) component is preferably 1% by mass or more, more preferably 2% by mass or more, and even more preferably 3% by mass or more, and is preferably 15% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less, when the nonvolatile components in the resin composition are taken as 100% by mass. In the present invention, the content of each component in the resin composition is the value when the nonvolatile components in the resin composition are taken as 100% by mass, unless otherwise specified.

[0024] <(B) Active ester curing agent> The resin composition contains an active ester-based curing agent (B) as the component (B). The use of the active ester-based curing agent can improve the dielectric tangent, resulting in excellent peel strength. The component (B) may be used alone or in combination of two or more types.

[0025] As the (B) active ester curing agent, generally, a compound having two or more highly reactive ester groups in one molecule, such as phenol esters, thiophenol esters, N-hydroxyamine esters, and esters of heterocyclic hydroxy compounds, is preferably used. The active ester curing agent is preferably one obtained by a condensation reaction between a carboxylic acid compound and / or a thiocarboxylic acid compound and a hydroxy compound and / or a thiol compound. In particular, from the viewpoint of improving heat resistance, an active ester curing agent obtained from a carboxylic acid compound and a hydroxy compound is preferred, and an active ester curing agent obtained from a carboxylic acid compound and a phenol compound and / or a naphthol compound is more preferred. Examples of the carboxylic acid compound include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, and pyromellitic acid. Examples of phenol compounds or naphthol compounds include hydroquinone, resorcin, bisphenol A, bisphenol F, bisphenol S, phenolphthaline, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucin, benzenetriol, dicyclopentadiene-type diphenol compounds, phenol novolac, etc. Here, the term "dicyclopentadiene-type diphenol compounds" refers to diphenol compounds obtained by condensing one molecule of dicyclopentadiene with two molecules of phenol.

[0026] Specifically, the (B) component may be a dicyclopentadiene-type active ester curing agent, a naphthalene-type active ester curing agent containing a naphthalene structure, an active ester curing agent containing an acetylated product of phenol novolac, or an active ester curing agent containing a benzoylated product of phenol novolac. Among them, the (B) component is more preferably one or more selected from a dicyclopentadiene-type active ester curing agent and a naphthalene-type active ester curing agent containing a naphthalene structure, and is even more preferably a naphthalene-type active ester curing agent containing a naphthalene structure. As the dicyclopentadiene-type active ester curing agent, an active ester curing agent containing a dicyclopentadiene diphenol structure is preferred. The "dicyclopentadiene diphenol structure" refers to a divalent structural unit consisting of phenylene-dicyclopentylene-phenylene.

[0027] (B) Commercially available active ester curing agents include "EXB9451", "EXB9460", "EXB9460S", "HPC-8000-65T", "HPC-8000H-65TM", and "EXB-8000L-65TM" (manufactured by DIC Corporation) as active ester curing agents containing a dicyclopentadiene-type diphenol structure; and "EXB9416-70BK", "EXB-8100L-65T", "EXB-8150L-65T", "EXB-8150-65T", "HPC-8150-60T", "HPC-8150-62T" (manufactured by DIC Corporation) and "PC1300-02-65T" (manufactured by DIC Corporation) as naphthalene-type active ester curing agents containing a naphthalene structure. Examples of such active ester curing agents include "DC808" (manufactured by Mitsubishi Chemical Corporation) as an active ester curing agent containing an acetylated product of phenol novolac; "YLH1026" (manufactured by Mitsubishi Chemical Corporation) as an active ester curing agent containing a benzoylated product of phenol novolac; "DC808" (manufactured by Mitsubishi Chemical Corporation) as an active ester curing agent which is an acetylated product of phenol novolac; "YLH1026" (manufactured by Mitsubishi Chemical Corporation), "YLH1030" (manufactured by Mitsubishi Chemical Corporation), "YLH1048" (manufactured by Mitsubishi Chemical Corporation) as active ester curing agents which are benzoylated products of phenol novolac; and "EXB-8500-65T" (manufactured by DIC Corporation).

[0028] From the viewpoint of being able to reduce the dielectric tangent and obtaining a cured product with excellent adhesion, the active ester group equivalent of the (B) active ester curing agent is preferably 50 g / eq. to 500 g / eq., more preferably 50 g / eq. to 400 g / eq., and even more preferably 100 g / eq. to 300 g / eq. The active ester group equivalent is the mass of the active ester curing agent containing one equivalent of active ester group.

[0029] The ratio of the amount of the (A) component to the (B) active ester curing agent is preferably 0.1 or more, more preferably 1 or more, and even more preferably 1.5 or more, and is preferably 10 or less, more preferably 8 or less, and even more preferably 5 or less, in terms of the ratio of [total number of active groups of the active ester curing agent] / [total number of epoxy groups of the (A) component]. Here, the "number of epoxy groups of the (A) component" refers to the total value of all values ​​obtained by dividing the mass of the non-volatile components of the epoxy resin present in the resin composition by the epoxy equivalent. In addition, the "number of active groups of the active ester curing agent" refers to the total value of all values ​​obtained by dividing the mass of the non-volatile components of the active ester curing agent present in the resin composition by the active ester group equivalent. By setting the ratio of the amount of the (A) and (B) active ester curing agents within this range, it is possible to obtain the effects of the present invention remarkably.

[0030] From the viewpoint of lowering the dielectric tangent and obtaining a cured product with excellent peel strength, the content of the (B) active ester curing agent is preferably 1% by mass or more, more preferably 5% by mass or more, and even more preferably 10% by mass or more, based on 100% by mass of the non-volatile components in the resin composition. The upper limit is preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 20% by mass or less.

[0031] <(C) Inorganic filler> In addition to the above-mentioned components, the resin composition may contain an inorganic filler (C) as an optional component. By including the inorganic filler (C) in the resin composition, it is possible to obtain a cured product having an excellent dielectric loss tangent.

[0032] As the material of the inorganic filler, an inorganic compound is used. Examples of the material of the inorganic filler include silica, alumina, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate titanate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium tungstate phosphate. Among these, silica is particularly suitable. Examples of silica include amorphous silica, fused silica, crystalline silica, synthetic silica, and hollow silica. Moreover, as the silica, spherical silica is preferable. (C) The inorganic filler may be used alone or in combination of two or more types.

[0033] (C) Commercially available inorganic fillers include, for example, "UFP-30" manufactured by Denka Chemical Industry Co., Ltd.; "SP60-05" and "SP507-05" manufactured by Nippon Steel & Sumitomo Metal Materials Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", and "YA010C" manufactured by Admatechs Co., Ltd.; "UFP-30" manufactured by Denka Company, Ltd.; "Silfill NSS-3N", "Silfill NSS-4N", and "Silfill NSS-5N" manufactured by Tokuyama Corporation; and "SC2500SQ", "SO-C4", "SO-C2", "SO-C1", and "SC2050-SXF" manufactured by Admatechs Co., Ltd.

[0034] From the viewpoint of significantly obtaining the desired effects of the present invention, the average particle size of the (C) inorganic filler is preferably 0.01 μm or more, more preferably 0.05 μm or more, particularly preferably 0.1 μm or more, and is preferably 5 μm or less, more preferably 2 μm or less, and even more preferably 1 μm or less.

[0035] (C) The average particle size of the inorganic filler can be measured by a laser diffraction / scattering method based on the Mie scattering theory. Specifically, the particle size distribution of the inorganic filler is prepared on a volume basis using a laser diffraction / scattering particle size distribution measuring device, and the median diameter is used as the average particle size. The measurement sample can be prepared by weighing 100 mg of the inorganic filler, 10 g of methyl ethyl ketone, and 0.1 g of a dispersant ("SN9228" manufactured by San Nopco) into a vial and dispersing the mixture for 10 minutes using ultrasonic waves. The measurement sample is measured using a laser diffraction particle size distribution measuring device with blue and red wavelengths as the light source, and the particle size distribution of the inorganic filler on a volume basis is measured using a flow cell method, and the average particle size is calculated from the obtained particle size distribution as the median diameter. Examples of the laser diffraction particle size distribution measuring device include "LA-960" manufactured by Horiba, Ltd. and "SALD-2200" manufactured by Shimadzu Corporation.

[0036] The specific surface area of ​​the (C) inorganic filler is preferably 1 m or less from the viewpoint of significantly obtaining the desired effects of the present invention. 2 / g or more, more preferably 2m 2 / g or more, particularly preferably 3m 2 / g or more. There is no particular upper limit, but it is preferably 60m 2 / g or less, 50m 2 / g or less or 40m 2 The specific surface area is measured by using a BET fully automatic specific surface area measuring device (Macsorb HM-1210 manufactured by Mountec Co., Ltd.) to adsorb nitrogen gas onto the surface of the sample, and then calculating the specific surface area using the BET multipoint method.

[0037] (C) The inorganic filler is preferably treated with a surface treatment agent from the viewpoint of improving moisture resistance and dispersibility. Examples of the surface treatment agent include fluorine-containing silane coupling agents such as 3,3,3-trifluoropropyltrimethoxysilane; aminosilane coupling agents such as 3-aminopropyltriethoxysilane, N-phenyl-8-aminooctyl-trimethoxysilane, and N-phenyl-3-aminopropyltrimethoxysilane; epoxysilane coupling agents such as 3-glycidoxypropyltrimethoxysilane; mercaptosilane coupling agents such as 3-mercaptopropyltrimethoxysilane; silane coupling agents; alkoxysilanes such as phenyltrimethoxysilane; organosilazane compounds such as hexamethyldisilazane, and titanate coupling agents. The surface treatment agent may be used alone or in any combination of two or more.

[0038] Examples of commercially available surface treatment agents include Shin-Etsu Chemical Co., Ltd.'s "KBM403" (3-glycidoxypropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM803" (3-mercaptopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBE903" (3-aminopropyltriethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "SZ-31" (hexamethyldisilazane), Shin-Etsu Chemical Co., Ltd.'s "KBM103" (phenyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM-4803" (long-chain epoxy-type silane coupling agent), and Shin-Etsu Chemical Co., Ltd.'s "KBM-7103" (3,3,3-trifluoropropyltrimethoxysilane).

[0039] The degree of surface treatment with the surface treatment agent is preferably within a predetermined range from the viewpoint of improving the dispersibility of the inorganic filler. Specifically, 100 parts by mass of the inorganic filler is preferably surface-treated with 0.2 parts by mass to 5 parts by mass of the surface treatment agent, more preferably 0.2 parts by mass to 3 parts by mass, and even more preferably 0.3 parts by mass to 2 parts by mass.

[0040] The degree of surface treatment with the surface treatment agent can be evaluated by the amount of carbon per unit surface area of ​​the inorganic filler. From the viewpoint of improving the dispersibility of the inorganic filler, the amount of carbon per unit surface area of ​​the inorganic filler is set to 0.02 mg / m 2 More than 0.1 mg / m is preferable. 2 More preferably, 0.2 mg / m or more 2 On the other hand, from the viewpoint of suppressing an increase in the melt viscosity of the resin varnish and the melt viscosity in the form of a sheet, it is more preferable that the content is 1 mg / m 2 Less than 0.8 mg / m is preferred. 2 Less than 0.5 mg / m is more preferable. 2 The following is even more preferred:

[0041] (C) The amount of carbon per unit surface area of ​​the inorganic filler can be measured after the surface-treated inorganic filler is washed with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK as a solvent is added to the inorganic filler that has been surface-treated with a surface treatment agent, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the solid content, the amount of carbon per unit surface area of ​​the inorganic filler can be measured using a carbon analyzer. As the carbon analyzer, the "EMIA-320V" manufactured by Horiba, Ltd., or the like can be used.

[0042] From the viewpoint of obtaining the effects of the present invention prominently, the content of the (C) inorganic filler is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more, and is preferably 90% by mass or less, more preferably 85% by mass or less, and even more preferably 80% by mass or less, when the non-volatile components in the resin composition are taken as 100% by mass.

[0043] <(D) Elastomer> The resin composition may contain an optional component (D) elastomer in addition to the above-mentioned components. The elastomer as the component (D) is a resin having flexibility, and is preferably a resin having rubber elasticity or a resin exhibiting rubber elasticity by polymerizing with another component. Examples of rubber elasticity include resins exhibiting an elastic modulus of 1 GPa or less when a tensile test is performed at a temperature of 25°C and a humidity of 40% RH according to the Japanese Industrial Standards (JIS K7161). The component (D) may be used alone or in combination of two or more types.

[0044] One embodiment of the (D) component includes a resin having one or more structures selected from a polybutadiene structure, a polysiloxane structure, a poly(meth)acrylate structure, a polyalkylene structure, a polyalkyleneoxy structure, a polyisoprene structure, a polyisobutylene structure, and a polycarbonate structure in the molecule. These are preferably resins having one or more structures selected from a polybutadiene structure, a poly(meth)acrylate structure, a polyalkyleneoxy structure, a polyisoprene structure, a polyisobutylene structure, and a polycarbonate structure. Note that the term "(meth)acrylate" includes both methacrylate and acrylate. These structures may be included in the main chain or in the side chain.

[0045] The (D) component is preferably high molecular weight from the viewpoint of obtaining the effects of the present invention significantly. The number average molecular weight (Mn) of the (D) component is preferably 1,000 or more, more preferably 1,500 or more, further preferably 2,000 or more, 2,500 or more, 3,000 or more, 4,000 or more, or 5,000 or more. The upper limit of Mn is preferably 1,000,000 or less, more preferably 900,000 or less, 800,000 or less, or 700,000 or less. The number average molecular weight (Mn) can be measured as a polystyrene equivalent value by gel permeation chromatography (GPC).

[0046] From the viewpoint of obtaining the effects of the present invention more prominently, the component (D) is preferably one or more selected from resins having a glass transition temperature (Tg) of 25° C. or less and resins that are liquid at 25° C. Here, for a resin with multiple observed Tg, if the lowest Tg is 25° C. or less, it corresponds to a "resin having a Tg of 25° C. or less." The glass transition temperature can be measured by DSC (differential scanning calorimetry).

[0047] For resins having a Tg of 25° C. or less, the Tg is preferably 20° C. or less, more preferably 15° C. or less. The lower limit of the Tg is not particularly limited, but can usually be −50° C. or more. Furthermore, for resins that are liquid at 25° C., they are preferably liquid at 20° C. or less, more preferably liquid at 15° C. or less.

[0048] From the viewpoint of achieving the remarkable effects of the present invention, it is preferable that the component (D) has a functional group capable of reacting with the component (A), etc. The functional group capable of reacting with the component (A) etc. also includes a functional group that appears upon heating.

[0049] The functional group is preferably one or more functional groups selected from the group consisting of a hydroxy group, a carboxy group, an acid anhydride group, a phenolic hydroxyl group, an epoxy group, an isocyanate group, and a urethane group. Among them, the functional group is preferably a hydroxy group, an acid anhydride group, a phenolic hydroxyl group, an epoxy group, an isocyanate group, and a urethane group, and more preferably a hydroxy group, an acid anhydride group, a phenolic hydroxyl group, and an epoxy group. However, when an epoxy group is included as a functional group, the number average molecular weight (Mn) is preferably 5,000 or more.

[0050] The (D) elastomer may be, for example, a resin containing a polybutadiene structure. The polybutadiene structure may be contained in the main chain or in the side chain. The polybutadiene structure may be partially or entirely hydrogenated. A resin containing a polybutadiene structure may be called a "polybutadiene resin". Specific examples of polybutadiene resins include "Ricon 130MA8", "Ricon 130MA13", "Ricon 130MA20", "Ricon 131MA5", "Ricon 131MA10", "Ricon 131MA17", "Ricon 131MA20", and "Ricon 184MA6" (polybutadiene containing acid anhydride groups), Nippon Soda's "JP-100", "JP-200" (epoxidized polybutadiene), "GQ-1000" (polybutadiene with hydroxyl and carboxyl groups introduced), "G-1000", "G-2000", "G-3000" (polybutadiene with hydroxyl groups at both ends), "GI-1000", "GI-2000", "GI-3000" (polybutadiene with hydrogenated hydroxyl groups at both ends), Daicel Examples of the polybutadiene resin include "PB3600", "PB4700" (polybutadiene-skeleton epoxy resin), "Epofriend A1005", "Epofriend A1010", and "Epofriend A1020" (epoxidized styrene, butadiene and styrene block copolymer) manufactured by Nagase Chemtex Corporation, "FCA-061L" (hydrogenated polybutadiene-skeleton epoxy resin) and "R-45EPT" (polybutadiene-skeleton epoxy resin) manufactured by Nagase Chemtex Corporation. Examples of the polybutadiene resin include hydroxyl-terminated polybutadiene, linear polymers made from diisocyanate compounds and tetrabasic acid anhydrides (polymers described in JP-A-2006-37083 and WO-A-2008 / 153208), and phenolic hydroxyl-containing butadienes. The content of the butadiene structure in the polymer is preferably 50% by mass or more, more preferably 60% by mass to 95% by mass. For details of the polymer, reference can be made to the descriptions in JP-A-2006-37083 and WO-A-2008 / 153208, the contents of which are incorporated herein by reference.

[0051] (D) Elastomers include, for example, resins containing a poly(meth)acrylate structure. Resins containing a poly(meth)acrylate structure are sometimes called "poly(meth)acrylic resins." Specific examples of poly(meth)acrylic resins include Teisan Resin manufactured by Nagase ChemteX Corporation, and ME-2000, W-116.3, W-197C, KG-25, and KG-3000 manufactured by Negami Chemical Industries, Ltd.

[0052] (D) elastomers include, for example, resins containing a polycarbonate structure. Resins containing a polycarbonate structure are sometimes called "polycarbonate resins". Specific examples of polycarbonate resins include "T6002" and "T6001" (polycarbonate diols) manufactured by Asahi Kasei Chemicals Corporation, and "C-1090", "C-2090", and "C-3090" (polycarbonate diols) manufactured by Kuraray Co., Ltd. In addition, linear polyimides made from hydroxyl-terminated polycarbonates, diisocyanate compounds, and tetrabasic acid anhydrides can also be used. The content of the carbonate structure in the polyimide resin is preferably 60% by mass to 95% by mass, more preferably 75% by mass to 85% by mass. For details of the polyimide resin, refer to the description in International Publication No. WO 2016 / 129541, the contents of which are incorporated herein by reference.

[0053] (D) Elastomers include, for example, resins containing a polysiloxane structure. Resins containing a polysiloxane structure are sometimes called "siloxane resins." Specific examples of siloxane resins include "SMP-2006," "SMP-2003PGMEA," and "SMP-5005PGMEA" manufactured by Shin-Etsu Silicone Co., Ltd., and linear polyimides made from amine-terminated polysiloxanes and tetrabasic acid anhydrides (see, for example, International Publication No. 2010 / 053185, JP 2002-12667 A and JP 2000-319386 A).

[0054] Examples of the (D) elastomer include resins containing a polyalkylene structure or a polyalkyleneoxy structure. A resin containing a polyalkylene structure may be referred to as an "alkylene resin". A resin containing a polyalkyleneoxy structure may be referred to as an "alkyleneoxy resin". The polyalkyleneoxy structure is preferably a polyalkyleneoxy structure having 2 to 15 carbon atoms, more preferably a polyalkyleneoxy structure having 3 to 10 carbon atoms, and particularly preferably a polyalkyleneoxy structure having 5 to 6 carbon atoms. Specific examples of the alkylene resin and the alkyleneoxy resin include "PTXG-1000" and "PTXG-1800" manufactured by Asahi Kasei Fibers Corporation.

[0055] (D) The elastomer may be, for example, a resin containing a polyisoprene structure. A resin containing a polyisoprene structure may be called an "isoprene resin." Specific examples of the isoprene resin include "KL-610" and "KL613" manufactured by Kuraray Co., Ltd.

[0056] (D) Elastomers include, for example, resins containing a polyisobutylene structure. Resins containing a polyisobutylene structure are sometimes called "isobutylene resins." Specific examples of isobutylene resins include Kaneka Corporation's "SIBSTAR-073T" (styrene-isobutylene-styrene triblock copolymer) and "SIBSTAR-042D" (styrene-isobutylene diblock copolymer).

[0057] (D) Elastomers include, for example, resins containing a polystyrene structure. Resins containing a polystyrene structure are sometimes called "styrene resins". Examples of styrene resins include styrene-butadiene-styrene block copolymers (SBS), styrene-isoprene-styrene block copolymers (SIS), styrene-ethylene-butylene-styrene block copolymers (SEBS), styrene-ethylene-propylene-styrene block copolymers (SEPS), styrene-ethylene-ethylene-propylene-styrene block copolymers (SEEPS), styrene-butadiene-butylene-styrene block copolymers (SBBS), styrene-butadiene diblock copolymers, hydrogenated styrene-butadiene block copolymers, hydrogenated styrene-isoprene block copolymers, and hydrogenated styrene-butadiene random copolymers. Specific examples of styrene resins include hydrogenated styrene-based thermoplastic elastomers "H1041", "Tuftec H1043", "Tuftec P2000", and "Tuftec MP10" (manufactured by Asahi Kasei Corporation); epoxidized styrene-butadiene thermoplastic elastomers "Epofriend AT501" and "CT310" (manufactured by Daicel Corporation); modified styrene-based elastomers having hydroxyl groups "Septon HG252" (manufactured by Kuraray Co., Ltd.); modified styrene-based elastomers having carboxyl groups "Tuftec N503M", modified styrene-based elastomers having amino groups "Tuftec N501", modified styrene-based elastomers having acid anhydride groups "Tuftec M1913" (manufactured by Asahi Kasei Chemicals Corporation); unmodified styrene-based elastomers "Septon S8104" (manufactured by Kuraray Co., Ltd.); and styrene-ethylene / butylene-styrene block copolymers "FG1924" (manufactured by Kraton Co., Ltd.).

[0058] Another preferred embodiment of the (D) component includes an organic filler as the (D) component. As the organic filler, a wide variety of organic fillers including a rubber component can be used. Examples of the rubber component included in the organic filler include silicone-based elastomers such as polydimethylsiloxane; olefin-based thermoplastic elastomers such as polybutadiene, polyisoprene, polychlorobutadiene, ethylene-vinyl acetate copolymer, styrene-butadiene copolymer, styrene-isoprene copolymer, styrene-isobutylene copolymer, acrylonitrile-butadiene copolymer, isoprene-isobutylene copolymer, isobutylene-butadiene copolymer, ethylene-propylene-diene terpolymer, and ethylene-propylene-butene terpolymer; and thermoplastic elastomers such as acrylic thermoplastic elastomers such as polypropyl(meth)acrylate, polybutyl(meth)acrylate, polycyclohexyl(meth)acrylate, and polyoctyl(meth)acrylate. Furthermore, silicone-based rubbers such as polyorganosiloxane rubber may be mixed into the rubber component. The rubber component contained in the rubber particles has a Tg of, for example, 0° C. or lower, preferably −10° C. or lower, more preferably −20° C. or lower, and even more preferably −30° C. or lower.

[0059] One embodiment of the organic filler is a core-shell type rubber particle consisting of a core particle containing the above-mentioned rubber component and a shell part obtained by graft copolymerization of a monomer component copolymerizable with the rubber component contained in the core particle. Here, the core-shell type does not necessarily refer only to those in which the core particle and the shell part are clearly distinguishable, but also includes those in which the boundary between the core particle and the shell part is unclear, and the core particle does not necessarily have to be completely covered with the shell part.

[0060] Specific examples of organic fillers containing a rubber component include, for example, "CHT" manufactured by Cheil Industries; "B602" manufactured by UMGABS; "Paraloid EXL-2602", "Paraloid EXL-2603", "Paraloid EXL-2655", "Paraloid EXL-2311", "Paraloid-EXL2313", "Paraloid EXL-2315", "Paraloid KM-330", "Paraloid KM-336P", "Paraloid KCZ-201" manufactured by Kureha Chemical Industry Co., Ltd.; and "Metabrene C" manufactured by Mitsubishi Rayon Co., Ltd. -223A", "Metabrene E-901", "Metabrene S-2001", "Metabrene W-450A", "Metabrene SRK-200", "Kane Ace M-511", "Kane Ace M-600", "Kane Ace M-400", "Kane Ace M-580", "Kane Ace MR-01" manufactured by Kaneka Corporation, "Staphyloid AC3355", "Staphyloid AC3816", "Staphyloid AC3832", "Staphyloid AC4030", "Staphyloid AC3364" manufactured by Aica Kogyo Co., Ltd. These are core-shell type rubber particles.

[0061] From the viewpoint of obtaining the effects of the present invention prominently, the content of the (D) component, when the total amount of non-volatile components in the resin composition is taken as 100 mass%, is preferably 0.5 mass% or more, more preferably 1 mass% or more, and even more preferably 1.5 mass% or more, and is preferably 5 mass% or less, more preferably 4 mass% or less, and even more preferably 3 mass% or less.

[0062] <(E) High molecular weight component> In addition to the above-mentioned components, the resin composition may further contain a high molecular weight component as an optional component (E). The component (E) may be used alone or in combination of two or more types.

[0063] From the viewpoint of obtaining a cured product with an even more excellent dielectric tangent, the weight average molecular weight (Mw) of the (E) component is preferably 5000 or more, more preferably 8000 or more, and even more preferably 10000 or more. There is no particular upper limit to the Mw, but it is preferably 100000 or less, more preferably 80000 or less, and even more preferably 50000 or less. The Mw of the (E) component can be measured as a polystyrene-equivalent value by gel permeation chromatography (GPC).

[0064] Examples of the (E) component include thermoplastic resins such as phenoxy resins, polyimide resins, polycarbonate resins, polyvinyl acetal resins, polyolefin resins, polyamideimide resins, polyetherimide resins, polysulfone resins, polyethersulfone resins, polyphenylene ether resins, polyetheretherketone resins, polystyrene resins, and polyester resins. Among these, from the viewpoint of obtaining a cured product excellent in dielectric tangent, it is preferable that the (E) component contains at least one selected from phenoxy resins, polyimide resins, and polycarbonate resins, and phenoxy resins are more preferable.

[0065] Examples of the phenoxy resin include phenoxy resins having one or more skeletons selected from the group consisting of bisphenol A skeleton, bisphenol F skeleton, bisphenol S skeleton, bisphenolacetophenone skeleton, novolac skeleton, biphenyl skeleton, fluorene skeleton, dicyclopentadiene skeleton, norbornene skeleton, naphthalene skeleton, anthracene skeleton, adamantane skeleton, terpene skeleton, and trimethylcyclohexane skeleton. The terminal of the phenoxy resin may be any functional group such as a phenolic hydroxyl group or an epoxy group.

[0066] Commercially available phenoxy resins include, for example, "1256" and "4250" manufactured by Mitsubishi Chemical Corporation (both of which are phenoxy resins containing a bisphenol A skeleton); "YX8100" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol S skeleton); "YX6954" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol acetophenone skeleton); "FX280" and "FX293" manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YL7500BH30", "YX6954BH30", "YX7553", "YX7553BH30", "YL7769BH30", "YL6794", "YL7213", "YL7290", and "YL7482" manufactured by Mitsubishi Chemical Corporation.

[0067] The polyimide resin may be a resin having an imide structure. The polyimide resin may generally be obtained by an imidization reaction between a diamine compound and an acid anhydride. The polyimide resin may be a commercially available product, such as "Rikacoat SN20" and "Rikacoat PN20" manufactured by New Japan Chemical Co., Ltd.

[0068] Polycarbonate resins are resins having a carbonate structure. Examples of such resins include carbonate resins having no reactive group, hydroxyl group-containing carbonate resins, phenolic hydroxyl group-containing carbonate resins, carboxyl group-containing carbonate resins, acid anhydride group-containing carbonate resins, isocyanate group-containing carbonate resins, urethane group-containing carbonate resins, and epoxy group-containing carbonate resins. The reactive group here refers to a functional group that can react with other components, such as a hydroxyl group, a phenolic hydroxyl group, a carboxyl group, an acid anhydride group, an isocyanate group, a urethane group, and an epoxy group.

[0069] Commercially available polycarbonate resins can be used, including "FPC0220" and "FPC2136" manufactured by Mitsubishi Gas Chemical Co., "T6002" and "T6001" (polycarbonate diols) manufactured by Asahi Kasei Chemicals Corporation, and "C-1090", "C-2090", and "C-3090" (polycarbonate diols) manufactured by Kuraray Co., Ltd.

[0070] From the viewpoint of obtaining the effects of the present invention prominently, the content of the (E) component is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, and even more preferably 0.5% by mass or more, and is preferably 5% by mass or less, more preferably 4% by mass or less, and even more preferably 3% by mass or less, based on 100% by mass of the non-volatile components in the resin composition.

[0071] <(F) Curing accelerator> The resin composition may contain (F) a curing accelerator as an optional component in addition to the above-mentioned components. Examples of the (F) curing accelerator include phosphorus-based curing accelerators, amine-based curing accelerators, imidazole-based curing accelerators, guanidine-based curing accelerators, and metal-based curing accelerators, and phosphorus-based curing accelerators, amine-based curing accelerators, imidazole-based curing accelerators, and metal-based curing accelerators are preferred, and amine-based curing accelerators and imidazole-based curing accelerators are more preferred. The curing accelerator may be used alone or in combination of two or more types.

[0072] Examples of the phosphorus-based curing accelerator include triphenylphosphine, phosphonium borate compounds, tetraphenylphosphonium tetraphenylborate, n-butylphosphonium tetraphenylborate, tetrabutylphosphonium decanoate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, butyltriphenylphosphonium thiocyanate, and the like, with triphenylphosphine and tetrabutylphosphonium decanoate being preferred.

[0073] Examples of the amine curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)-undecene, with 4-dimethylaminopyridine being preferred.

[0074] Examples of the imidazole curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2, 4-Diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-furan Examples of the imidazole compounds include imidazole compounds such as 2-ethyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, and 2-phenylimidazoline, as well as adducts of imidazole compounds and epoxy resins. Of these, 2-ethyl-4-methylimidazole and 1-benzyl-2-phenylimidazole are preferred.

[0075] As the imidazole-based curing accelerator, a commercially available product may be used, for example, "P200-H50" manufactured by Mitsubishi Chemical Corporation.

[0076] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, and 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene. Examples of such biguanide include o-[4.4.0]dec-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-n-butylbiguanide, 1-n-octadecylbiguanide, 1,1-dimethylbiguanide, 1,1-diethylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, 1-phenylbiguanide, and 1-(o-tolyl)biguanide. Of these, dicyandiamide and 1,5,7-triazabicyclo[4.4.0]dec-5-ene are preferred.

[0077] Examples of metal-based curing accelerators include organometallic complexes or organometallic salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organometallic complexes include organocobalt complexes such as cobalt(II) acetylacetonate and cobalt(III) acetylacetonate, organocopper complexes such as copper(II) acetylacetonate, organozinc complexes such as zinc(II) acetylacetonate, organoiron complexes such as iron(III) acetylacetonate, organonickel complexes such as nickel(II) acetylacetonate, and organomanganese complexes such as manganese(II) acetylacetonate. Examples of organometallic salts include zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate.

[0078] From the viewpoint of obtaining the effects of the present invention prominently, the content of the (F) component, when the non-volatile components in the resin composition are taken as 100 mass%, is preferably 0.01 mass% or more, more preferably 0.03 mass% or more, even more preferably 0.05 mass% or more, and is preferably 1 mass% or less, more preferably 0.8 mass% or less, even more preferably 0.5 mass% or less.

[0079] <(G) Epoxy resin other than component (A)> In addition to the components described above, the resin composition may contain an optional component (G) an epoxy resin other than the component (A).

[0080] Examples of the (G) component include bixylenol type epoxy resins, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bisphenol AF type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol novolac type epoxy resins, phenol novolac type epoxy resins, tert-butyl-catechol type epoxy resins, naphthalene type epoxy resins, naphthol type epoxy resins, anthracene type epoxy resins, glycidylamine type epoxy resins, glycidyl ester type epoxy resins, cresol novolac type epoxy resins, biphenyl type epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, alicyclic epoxy resins, heterocyclic epoxy resins, spiro ring-containing epoxy resins, cyclohexane type epoxy resins, cyclohexane dimethanol type epoxy resins, naphthylene ether type epoxy resins, trimethylol type epoxy resins, tetraphenylethane type epoxy resins, etc. The (G) component may be used alone or in combination of two or more.

[0081] Component (G) includes epoxy resins that are liquid at a temperature of 20° C. (hereinafter referred to as "liquid epoxy resins") and epoxy resins that are solid at a temperature of 20° C. (hereinafter referred to as "solid epoxy resins"). The resin composition of the present invention may contain only a liquid epoxy resin, may contain only a solid epoxy resin, or may contain a combination of a liquid epoxy resin and a solid epoxy resin.

[0082] Specific examples of liquid epoxy resins include "HP4032", "HP4032D", and "HP4032SS" (naphthalene type epoxy resins) manufactured by DIC Corporation; "828US", "jER828EL", "825", and "Epikote 828EL" (bisphenol A type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER807" and "1750" (bisphenol F type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER152" (phenol novolac type epoxy resin) manufactured by Mitsubishi Chemical Corporation; and "630" and "630LSD" (glycidylamine type epoxy resins) manufactured by Mitsubishi Chemical Corporation. epoxy resin); Nippon Steel & Sumitomo Metal Chemical's "ZX1059" (a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin); Nagase ChemteX's "EX-721" (glycidyl ester type epoxy resin); Daicel's "Celloxide 2021P" (alicyclic epoxy resin with an ester skeleton); Daicel's "PB-3600" (epoxy resin with a butadiene structure); Nippon Steel & Sumitomo Metal Chemical's "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane type epoxy resin), etc.

[0083] Specific examples of solid epoxy resins include "HP4032H" (naphthalene type epoxy resin) manufactured by DIC Corporation; "HP-4700" and "HP-4710" (naphthalene type tetrafunctional epoxy resins) manufactured by DIC Corporation; "N-690" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "N-695" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "HP-7200HH", "HP-7200H", and "HP-7200" (dicyclopentadiene type epoxy resins) manufactured by DIC Corporation. epoxy resins); DIC's "EXA-7311", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", and "HP6000" (naphthylene ether type epoxy resins); Nippon Kayaku's "EPPN-502H" (trisphenol type epoxy resins); Nippon Kayaku's "NC7000L" (naphthol novolac type epoxy resins); Nippon Kayaku's "NC3000H", "NC3000", "NC3000L", and "NC3100" (biphenyl type epoxy resins) epoxy resin); "ESN475V" (naphthol type epoxy resin) manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd.; "ESN485" (naphthol novolac type epoxy resin) manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd.; "ESN-4100V", "ESN-4100VEK75" (naphthalene skeleton epoxy resin); "YX4000H", "YX4000", "YL6121" (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "YX4000HK" (bixylenol type epoxy resin) manufactured by Mitsubishi Chemical Corporation; Examples of epoxy resins that can be used include "YX8800" (anthracene type epoxy resin) manufactured by Osaka Gas Chemical Co., Ltd.; "PG-100" and "CG-500" manufactured by Osaka Gas Chemical Co., Ltd.; "YL7760" (bisphenol AF type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "YL7800" (fluorene type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "jER1010" (solid bisphenol A type epoxy resin) manufactured by Mitsubishi Chemical Corporation; and "jER1031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical Corporation.

[0084] The epoxy equivalent of the (G) component is preferably 50 g / eq. to 5000 g / eq., more preferably 50 g / eq. to 3000 g / eq., even more preferably 80 g / eq. to 2000 g / eq., and even more preferably 110 g / eq. to 1000 g / eq. The epoxy equivalent is the mass of the (G) component containing one equivalent of an epoxy group. This epoxy equivalent can be measured according to JIS K7236.

[0085] The weight average molecular weight (Mw) of the component (G) is preferably from 100 to 5000, more preferably from 250 to 3000, and even more preferably from 400 to 1500. The Mw of the component (G) can be measured by gel permeation chromatography (GPC) as a polystyrene-equivalent value.

[0086] From the viewpoint of obtaining the effects of the present invention prominently, the content of the (G) component is preferably 1% by mass or more, more preferably 2% by mass or more, and even more preferably 3% by mass or more, and is preferably 15% by mass or less, more preferably 10% by mass or less, and even more preferably 8% by mass or less, based on 100% by mass of the non-volatile components in the resin composition.

[0087] <(H) Hardeners other than component (B)> In addition to the above-mentioned components, the resin composition may further contain a curing agent other than the component (H) (B) as an optional component. Examples of the component (H) include a phenol-based curing agent, a naphthol-based curing agent, a benzoxazine-based curing agent, a cyanate ester-based curing agent, and a carbodiimide-based curing agent. Among them, from the viewpoint of improving the insulation reliability, the component (H) is preferably one or more of a phenol-based curing agent, a naphthol-based curing agent, a cyanate ester-based curing agent, and a carbodiimide-based curing agent, more preferably one of a phenol-based curing agent and a naphthol-based curing agent, and further preferably includes a phenol-based curing agent. The component (H) may be used alone or in combination of two or more.

[0088] As the phenol-based curing agent and naphthol-based curing agent, from the viewpoint of heat resistance and water resistance, a phenol-based curing agent having a novolac structure or a naphthol-based curing agent having a novolac structure is preferable. Also, from the viewpoint of adhesion to the conductor layer, a nitrogen-containing phenol-based curing agent is preferable, and a triazine skeleton-containing phenol-based curing agent is more preferable.

[0089] Specific examples of phenol-based curing agents and naphthol-based curing agents include, for example, "MEH-7700", "MEH-7810", and "MEH-7851" manufactured by Meiwa Kasei Co., Ltd., "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd., "SN170", "SN180", "SN190", "SN475", "SN485", "SN495", "SN-495V", "SN375", and "SN395" manufactured by Nippon Steel & Sumikin Chemical Co., Ltd., and "TD-2090", "LA-7052", "LA-7054", "LA-1356", "LA3018-50P", and "EXB-9500" manufactured by DIC Corporation.

[0090] Specific examples of benzoxazine-based curing agents include "HFB2006M" manufactured by Showa Polymer Co., Ltd., and "Pd" and "Fa" manufactured by Shikoku Chemical Industry Co., Ltd.

[0091] Examples of the cyanate ester curing agent include bifunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate, oligo(3-methylene-1,5-phenylene cyanate), 4,4'-methylenebis(2,6-dimethylphenyl cyanate), 4,4'-ethylidene diphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanate phenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanate phenyl-1-(methylethylidene))benzene, bis(4-cyanate phenyl)thioether, and bis(4-cyanate phenyl)ether; polyfunctional cyanate resins derived from phenol novolac and cresol novolac; and prepolymers in which these cyanate resins are partially converted to triazine. Specific examples of cyanate ester-based curing agents include "PT30" and "PT60" (phenol novolac type multifunctional cyanate ester resins), "ULL-950S" (multifunctional cyanate ester resin), "BA230", and "BA230S75" (prepolymers in which part or all of bisphenol A dicyanate has been converted to triazine to form a trimer), all of which are manufactured by Lonza Japan.

[0092] Specific examples of carbodiimide-based curing agents include "V-03" and "V-07" manufactured by Nisshinbo Chemical Inc.

[0093] When the curing agent is contained as the (H) component, the ratio of the amount of the (A) component to the (B) component and the (H) component is preferably in the range of 1:0.01 to 1:5, more preferably 1:0.05 to 1:3, and even more preferably 1:0.1 to 1:2, in terms of the ratio of [total number of epoxy groups in the (A) component]:[total number of active groups in the (B) component and the (H) component]. Here, the "number of epoxy groups in the (A) component" refers to the total value obtained by dividing the mass of the non-volatile component of the (A) component present in the resin composition by the epoxy equivalent. In addition, the "number of active groups in the (B) component and the (H) component" refers to the total value obtained by dividing the mass of the non-volatile component of the (B) component and the (H) component present in the resin composition by the active group equivalent. By setting the ratio of the amount of the (B) component and the (H) component to the (A) component within such a range, the effect of the present invention can be obtained remarkably.

[0094] When the curing agent is contained as the (H) component, the ratio of the amount of the (A) component to all the (H) components is preferably in the range of 1:0.01 to 1:1, more preferably 1:0.03 to 1:0.5, and even more preferably 1:0.05 to 1:0.3, in terms of the ratio of [total number of epoxy groups in the (A) component]:[total number of active groups in the (H) component]. Here, the "number of active groups in the (H) component" refers to the total value obtained by dividing the mass of the non-volatile components of the (H) component present in the resin composition by the active group equivalent. By setting the ratio of the amount of the (A) component to the (H) component within this range, the effects of the present invention can be obtained significantly.

[0095] From the viewpoint of significantly obtaining the desired effects of the present invention, the content of the (H) component, relative to 100 mass% of the non-volatile components in the resin composition, is preferably 0.1 mass% or more, more preferably 0.3 mass% or more, and more preferably 0.5 mass% or more, and is preferably 5 mass% or less, more preferably 3 mass% or less, and even more preferably 1 mass% or less.

[0096] <(I) Other additives> The resin composition may further contain other additives as optional components in addition to the above-mentioned components. Examples of such additives include thermoplastic resins, elastomers, organic fillers, thickeners, defoamers, leveling agents, adhesion promoters, flame retardants, etc. These may be used alone or in combination of two or more at any ratio.

[0097] The resin composition can be produced, for example, by mixing the above-mentioned components in any order. In addition, in the process of mixing each component, heating and / or cooling may be performed by appropriately adjusting the temperature. In addition, during or after mixing of each component, stirring may be performed using a stirring device such as a mixer to uniformly disperse each component. Furthermore, if necessary, the resin composition may be subjected to a degassing treatment.

[0098] <Physical properties and applications of resin compositions> Since the resin composition contains a combination of the component (A) and the component (B), it is possible to obtain a cured product that has a good dielectric tangent, excellent peel strength, and suppressed cracking after a desmear treatment.

[0099] The cured product obtained by thermally curing the resin composition at 190°C for 90 minutes has a low dielectric loss tangent. Therefore, when an insulating layer is formed with this cured product, an insulating layer with a low dielectric loss tangent can be obtained. For example, the dielectric loss tangent Df of the cured product obtained by curing the resin composition under the conditions described in the examples described later is preferably 0.010 or less, more preferably 0.005 or less, and even more preferably 0.004 or less. The lower limit of the dielectric loss tangent Df of the cured product is not particularly limited, but may be 0.001 or more. The dielectric loss tangent of the cured product can be measured by the method described in the examples.

[0100] The cured product obtained by thermally curing the resin composition at 190°C for 90 minutes exhibits the characteristic of a high glass transition temperature (Tg). Therefore, when an insulating layer is formed from this cured product, an insulating layer having a high glass transition temperature and excellent heat resistance can be obtained. The glass transition temperature is preferably 140°C or higher, more preferably 145°C or higher, and even more preferably 150°C or higher. The upper limit is not particularly limited, but may be 300°C or lower. The glass transition temperature can be measured according to the method described in the examples below.

[0101] The cured product obtained by thermally curing the resin composition at 190°C for 90 minutes exhibits the characteristic of high plating peel strength between the resin composition and the plating. Therefore, when an insulating layer is formed from this cured product, an insulating layer with high peel strength between the insulating layer and the plating conductor layer can be obtained. For example, when the insulating layer and the plating conductor layer are formed by the method described in the examples below, the plating peel strength between the insulating layer and the conductor layer can be preferably 0.1 kgf / cm or more, more preferably 0.2 kgf / cm or more, and particularly preferably 0.3 kgf / cm or more. The upper limit of the plating peel strength is not particularly limited, but can be, for example, 10.0 kgf / cm or less. The plating peel strength can be measured by the method described in the examples.

[0102] A cured product obtained by thermally curing a resin composition at 170°C for 30 minutes usually exhibits the property of suppressing the occurrence of cracks after desmearing. Therefore, when an insulating layer is formed from this cured product, an insulating layer in which the occurrence of cracks after desmearing is suppressed can be obtained. Even when 100 copper pads of a circuit board after desmearing are observed, the number of cracks is 10 or less. The cracks after desmearing can be measured by the method described in the Examples.

[0103] A cured product obtained by thermally curing a resin composition at 190°C for 90 minutes usually exhibits the characteristic of a low coefficient of thermal expansion (CTE). Thus, an insulating layer having a low coefficient of thermal expansion can be obtained. The coefficient of thermal expansion is preferably 20 ppm / °C or less, more preferably 18 ppm / °C or less, and even more preferably 15 ppm / °C or less. The lower limit is not particularly limited, but may be 1 ppm / °C or more. The coefficient of thermal expansion can be measured according to the method described in the examples below.

[0104] The resin composition according to one embodiment of the present invention is suitable as a resin composition for insulating applications, and is particularly suitable as a resin composition for forming an insulating layer. Thus, for example, the resin composition is suitable as a resin composition for forming an insulating layer of a printed wiring board (a resin composition for forming an insulating layer of a printed wiring board). In addition, the resin composition is suitable as a resin composition for forming an insulating layer (a resin composition for forming an insulating layer for forming a conductor layer) for forming a conductor layer (including a rewiring layer) formed on the insulating layer. The resin composition can also be used in a wide range of applications in which the resin composition can be used, such as a resin sheet, a sheet-like laminate material such as a prepreg, a solder resist, an underfill material, a die bonding material, a semiconductor encapsulant, a hole filling resin, a component embedding resin, a multi-chip package, a package-on-package, a wafer-level package, a panel-level package, a system-in-package, etc.

[0105] Furthermore, for example, when a semiconductor chip package is manufactured through the following steps (1) to (6), the resin composition according to the present embodiment is also suitable as a resin composition for forming a rewiring formation layer as an insulating layer for forming a rewiring layer (resin composition for forming a rewiring formation layer) and as a resin composition for sealing a semiconductor chip (resin composition for sealing a semiconductor chip). When a semiconductor chip package is manufactured, a rewiring layer may be further formed on the sealing layer. (1) A step of laminating a temporary fixing film onto a substrate; (2) a step of temporarily fixing a semiconductor chip on a temporary fixing film; (3) forming an encapsulation layer on the semiconductor chip; (4) peeling the substrate and the temporary fixing film from the semiconductor chip; (5) forming a rewiring formation layer as an insulating layer on the surface of the semiconductor chip from which the base material and the temporary fixing film have been peeled off; and (6) A process of forming a rewiring layer as a conductor layer on the rewiring formation layer.

[0106] The above-mentioned resin composition can also be used when the printed wiring board is a circuit board with built-in components.

[0107] [Resin sheet] The resin sheet of the present invention includes a support and a resin composition layer formed from the resin composition of the present invention provided on the support.

[0108] The thickness of the resin composition layer is preferably 50 μm or less, more preferably 40 μm or less, and even more preferably 30 μm or less, from the viewpoint of making the printed wiring board thinner and being able to provide a cured product with excellent insulation even if the cured product of the resin composition is a thin film. The lower limit of the thickness of the resin composition layer is not particularly limited, but can usually be 5 μm or more.

[0109] Examples of the support include films made of plastic materials, metal foils, and release papers, with films made of plastic materials and metal foils being preferred.

[0110] When a film made of a plastic material is used as the support, examples of the plastic material include polyesters such as polyethylene terephthalate (hereinafter sometimes abbreviated as "PET") and polyethylene naphthalate (hereinafter sometimes abbreviated as "PEN"), polycarbonate (hereinafter sometimes abbreviated as "PC"), acrylics such as polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among these, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.

[0111] When a metal foil is used as the support, examples of the metal foil include copper foil, aluminum foil, etc., and copper foil is preferred. As the copper foil, a foil made of a single metal, copper, or an alloy of copper and another metal (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) may be used.

[0112] The surface of the support to be bonded to the resin composition layer may be subjected to a matte treatment, a corona treatment, or an antistatic treatment.

[0113] In addition, as the support, a support with a release layer having a release layer on the surface to be bonded to the resin composition layer may be used. The release agent used in the release layer of the support with a release layer may be, for example, one or more release agents selected from the group consisting of alkyd resins, polyolefin resins, urethane resins, and silicone resins. The support with a release layer may be a commercially available product, for example, "SK-1", "AL-5", and "AL-7" manufactured by Lintec Corporation, "Lumirror T60" manufactured by Toray Industries, Inc., "Purex" manufactured by Teijin Limited, and "Unipeel" manufactured by Unitika Limited, which are PET films having a release layer mainly composed of an alkyd resin-based release agent.

[0114] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, and more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, it is preferable that the total thickness of the support with a release layer is in the above range.

[0115] In one embodiment, the resin sheet may further include other layers as necessary. Examples of such other layers include a protective film equivalent to the support provided on the surface of the resin composition layer that is not bonded to the support (i.e., the surface opposite to the support). The thickness of the protective film is not particularly limited, but is, for example, 1 μm to 40 μm. By laminating the protective film, adhesion of dirt and the like to the surface of the resin composition layer and scratches can be suppressed.

[0116] The resin sheet can be produced, for example, by preparing a resin varnish by dissolving a resin composition in an organic solvent, applying this resin varnish onto a support using a die coater or the like, and then drying the same to form a resin composition layer.

[0117] Examples of organic solvents include ketones such as acetone, methyl ethyl ketone (MEK), and cyclohexanone; acetates such as ethyl acetate, butyl acetate, cellosolve acetate, propylene glycol monomethyl ether acetate, and carbitol acetate; carbitols such as cellosolve and butyl carbitol; aromatic hydrocarbons such as toluene and xylene; and amide solvents such as dimethylformamide, dimethylacetamide (DMAc), and N-methylpyrrolidone. The organic solvents may be used alone or in combination of two or more.

[0118] Drying may be performed by a known method such as heating or hot air blowing. Drying conditions are not particularly limited, but drying is performed so that the content of organic solvent in the resin composition layer becomes 10 mass % or less, preferably 5 mass % or less. Although it varies depending on the boiling point of the organic solvent in the resin varnish, for example, when a resin varnish containing 30 mass % to 60 mass % of organic solvent is used, the resin composition layer can be formed by drying at 50°C to 150°C for 3 minutes to 10 minutes.

[0119] The resin sheet can be stored in a rolled state. When the resin sheet has a protective film, it can be used by peeling off the protective film.

[0120] [Printed wiring board] A printed wiring board according to one embodiment of the present invention includes an insulating layer formed of a cured product obtained by curing the above-described resin composition.

[0121] The printed wiring board can be produced, for example, by using the above-mentioned resin sheet by a method including the following steps (I) and (II). (I) A step of laminating a resin sheet on an inner layer substrate such that a resin composition layer of the resin sheet is bonded to the inner layer substrate. (II) A step of curing the resin composition layer to form an insulating layer

[0122] The "inner layer substrate" used in step (I) is a member that becomes the substrate of the printed wiring board, and examples thereof include a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, and a thermosetting polyphenylene ether substrate. The substrate may have a conductor layer on one or both sides, and the conductor layer may be patterned. An inner layer substrate having a conductor layer formed on one or both sides of the substrate may be called an "inner layer circuit substrate". In addition, an intermediate product on which an insulating layer and / or a conductor layer is to be further formed during the manufacture of a printed wiring board is also included in the "inner layer substrate". When the printed wiring board is a circuit board with built-in components, an inner layer substrate with built-in components may be used.

[0123] The lamination of the inner layer substrate and the resin sheet can be carried out, for example, by thermocompression bonding the resin sheet to the inner layer substrate from the support side. Examples of the member for thermocompression bonding the resin sheet to the inner layer substrate (hereinafter also referred to as the "thermocompression bonding member") include a heated metal plate (such as a SUS plate) or a metal roll (such as a SUS roll). It is preferable to press the thermocompression member not directly onto the resin sheet, but via an elastic material such as heat-resistant rubber so that the resin sheet can sufficiently follow the surface irregularities of the inner layer substrate.

[0124] The lamination of the inner layer substrate and the resin sheet may be performed by a vacuum lamination method. In the vacuum lamination method, the thermocompression temperature is preferably in the range of 60°C to 160°C, more preferably in the range of 80°C to 140°C, the thermocompression pressure is preferably in the range of 0.098MPa to 1.77MPa, more preferably in the range of 0.29MPa to 1.47MPa, and the thermocompression time is preferably in the range of 20 seconds to 400 seconds, more preferably in the range of 30 seconds to 300 seconds. The lamination may be performed under reduced pressure conditions, preferably at a pressure of 26.7hPa or less.

[0125] The lamination can be performed by a commercially available vacuum laminator, such as a vacuum pressure laminator manufactured by Meiki Seisakusho Co., Ltd., a vacuum applicator manufactured by Nikko Materials Co., Ltd., or a batch type vacuum pressure laminator.

[0126] After lamination, the laminated resin sheet may be smoothed under atmospheric pressure, for example, by pressing a thermocompression member from the support side. The pressing conditions for the smoothing treatment may be the same as the thermocompression conditions for the lamination. The smoothing treatment may be performed using a commercially available laminator. The lamination and smoothing treatment may be performed consecutively using the commercially available vacuum laminator.

[0127] The support may be removed between step (I) and step (II) or after step (II).

[0128] In step (II), the resin composition layer is cured to form an insulating layer made of a cured product of the resin composition. The curing conditions for the resin composition layer are not particularly limited, and the conditions employed for forming an insulating layer of a printed wiring board may be used. The resin composition layer may be cured by irradiation with active energy rays such as ultraviolet rays, but is usually thermally cured by heating.

[0129] For example, the thermal curing conditions for the resin composition layer vary depending on the type of resin composition, but in one embodiment, the curing temperature is preferably 120° C. to 240° C., more preferably 150° C. to 220° C., and even more preferably 170° C. to 210° C. The curing time is preferably 5 minutes to 120 minutes, more preferably 10 minutes to 100 minutes, and even more preferably 15 minutes to 100 minutes.

[0130] Before the resin composition layer is thermally cured, the resin composition layer may be preheated at a temperature lower than the curing temperature. For example, prior to thermally curing the resin composition layer, the resin composition layer may be preheated at a temperature of 50° C. to 120° C., preferably 60° C. to 115° C., more preferably 70° C. to 110° C. for 5 minutes or more, preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and even more preferably 15 minutes to 100 minutes.

[0131] The method for producing a printed wiring board may further include the steps of (III) drilling holes in the insulating layer, (IV) roughening the insulating layer, and (V) forming a conductor layer. When the support is removed after step (II), the removal of the support may be performed between steps (II) and (III), between steps (III) and (IV), or between steps (IV) and (V). In addition, the steps (I) to (V) of forming the insulating layer and the conductor layer may be repeated to form a multilayer wiring board, as necessary.

[0132] Step (III) is a step of drilling holes in the insulating layer, which allows holes such as via holes and through holes to be formed in the insulating layer. Step (III) may be performed using, for example, a drill, a laser, plasma, etc., depending on the composition of the resin composition used to form the insulating layer. The dimensions and shape of the holes may be appropriately determined depending on the design of the printed wiring board.

[0133] Step (IV) is a step of roughening the insulating layer. Usually, smears are also removed in this step (IV). The procedure and conditions of the roughening treatment are not particularly limited. For example, the insulating layer can be roughened by carrying out a swelling treatment with a swelling liquid, a roughening treatment with an oxidizing agent, and a neutralization treatment with a neutralizing liquid in this order.

[0134] Examples of the swelling liquid used in the roughening treatment include an alkaline solution and a surfactant solution, and an alkaline solution is preferred. As the alkaline solution, a sodium hydroxide solution and a potassium hydroxide solution are more preferred. Examples of commercially available swelling liquids include "Swelling Dip Securigans P" and "Swelling Dip Securigans SBU" manufactured by Atotech Japan. The swelling treatment using the swelling liquid is not particularly limited, but can be performed by immersing the insulating layer in a swelling liquid at 30°C to 90°C for 1 to 20 minutes. From the viewpoint of suppressing the swelling of the resin of the insulating layer to an appropriate level, it is preferred to immerse the insulating layer in a swelling liquid at 40°C to 80°C for 5 to 15 minutes.

[0135] An example of an oxidizing agent used in the roughening treatment is an alkaline permanganate solution in which potassium permanganate or sodium permanganate is dissolved in an aqueous solution of sodium hydroxide. The roughening treatment using an oxidizing agent such as an alkaline permanganate solution is preferably performed by immersing the insulating layer in an oxidizing agent solution heated to 60°C to 100°C for 10 minutes to 30 minutes. The concentration of permanganate in the alkaline permanganate solution is preferably 5% by mass to 10% by mass. Examples of commercially available oxidizing agents include alkaline permanganate solutions such as "Concentrate Compact CP" and "Dosing Solution Securigans P" manufactured by Atotech Japan.

[0136] The neutralizing solution used in the roughening treatment is preferably an acidic aqueous solution, and a commercially available product is, for example, "Reduction Solution Securigant P" manufactured by Atotech Japan. Treatment with a neutralizing solution can be performed by immersing the surface that has been roughened with an oxidizing agent in a neutralizing solution at 30°C to 80°C for 5 to 30 minutes. From the viewpoint of workability, etc., a method in which the object that has been roughened with an oxidizing agent is immersed in a neutralizing solution at 40°C to 70°C for 5 to 20 minutes is preferred.

[0137] In one embodiment, the arithmetic mean roughness Ra of the insulating layer surface after the roughening treatment is preferably 500 nm or less, more preferably 400 nm or less, and even more preferably 300 nm or less. The lower limit is not particularly limited, and may be, for example, 1 nm or more, 2 nm or more, etc. The root mean square roughness (Rq) of the insulating layer surface after the roughening treatment is preferably 500 nm or less, more preferably 400 nm or less, and even more preferably 300 nm or less. The lower limit is not particularly limited, and may be, for example, 1 nm or more, 2 nm or more, etc. The arithmetic mean roughness (Ra) and root mean square roughness (Rq) of the insulating layer surface can be measured using a non-contact surface roughness meter.

[0138] Step (V) is a step of forming a conductor layer, and the conductor layer is formed on the insulating layer. The conductor material used for the conductor layer is not particularly limited. In a preferred embodiment, the conductor layer contains one or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin and indium. The conductor layer may be a single metal layer or an alloy layer, and examples of the alloy layer include layers formed from alloys of two or more metals selected from the above group (e.g., nickel-chromium alloy, copper-nickel alloy and copper-titanium alloy). Among these, from the viewpoints of versatility in forming the conductor layer, cost, ease of patterning, and the like, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of a nickel-chromium alloy, a copper-nickel alloy, or a copper-titanium alloy is preferred, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of a nickel-chromium alloy is more preferred, and a single metal layer of copper is even more preferred.

[0139] The conductor layer may be a single-layer structure, or a multi-layer structure in which two or more single metal layers or alloy layers made of different kinds of metals or alloys are laminated. When the conductor layer has a multi-layer structure, the layer in contact with the insulating layer is preferably a single metal layer of chromium, zinc or titanium, or an alloy layer of a nickel-chromium alloy.

[0140] The thickness of the conductor layer depends on the desired design of the printed wiring board, but is generally 3 μm to 35 μm, and preferably 5 μm to 30 μm.

[0141] The conductor layer is preferably formed by plating. For example, the surface of the insulating layer can be plated by a semi-additive method, a full-additive method, or the like to form a conductor layer having a desired wiring pattern. From the viewpoint of ease of production, it is preferable to form the conductor layer by the semi-additive method. An example of forming the conductor layer by the semi-additive method will be described below.

[0142] A plating seed layer is formed on the surface of the insulating layer by electroless plating. Then, a mask pattern is formed on the formed plating seed layer to expose a part of the plating seed layer corresponding to a desired wiring pattern. After a metal layer is formed on the exposed plating seed layer by electrolytic plating, the mask pattern is removed. Thereafter, unnecessary plating seed layer is removed by etching or the like to form a conductor layer having a desired wiring pattern.

[0143] [Semiconductor Devices] A semiconductor device according to an embodiment of the present invention includes the above-mentioned printed wiring board. This semiconductor device can be manufactured using the above-mentioned printed wiring board.

[0144] Examples of the semiconductor device include various semiconductor devices used in electric appliances (for example, computers, mobile phones, digital cameras, and televisions) and vehicles (for example, motorcycles, automobiles, trains, ships, and aircraft). EXAMPLES

[0145] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the following description, the terms "parts" and "%" used to express amounts refer to "parts by mass" and "% by mass", respectively, unless otherwise specified.

[0146] [Example 1] 3 parts of epoxy resin represented by the following formula (manufactured by Sumitomo Chemical Co., Ltd., "ELM-100H", epoxy equivalent 104g / eq.), 3 parts of biphenyl skeleton epoxy resin (manufactured by Nippon Kayaku Co., Ltd., "NC-3100", epoxy equivalent 258g / eq.), 6 parts of naphthalene skeleton epoxy resin (manufactured by DIC Corporation, "HP-4032-SS", epoxy equivalent 144g / eq.), 6 parts of naphthalene skeleton epoxy resin (manufactured by Nippon Steel Chemical & Material Co., Ltd., "ESN-4100VEK75", Epoxy equivalent 360 g / eq., MEK solution with 75% non-volatile content) 8 parts, active ester curing agent (DIC Corporation "HPC-8150-62T", toluene solution with 62% non-volatile content by mass, active ester group equivalent 234 g / eq.) 41.9 parts, inorganic filler (spherical silica (Admatechs Co., Ltd. "SO-C2", average particle size 0.5 μm, specific surface area 5.8 m) surface-treated with an amine-based alkoxysilane compound (Shin-Etsu Chemical Co., Ltd. "KBM573") 2 A resin varnish was obtained by mixing 150 parts of toluene (1.2 g / g), 4 parts of organic filler (DOW, "EXL-2655"), 6.7 parts of phenoxy resin ("YX7553BH30", a mixed solution of cyclohexanone and MEK with a non-volatile content of 30%), 0.1 parts of curing accelerator (Wako Pure Chemical Industries, 4-dimethylaminopyridine), and 0.1 parts of curing accelerator (Shikoku Kasei Corporation, imidazole compound "1B2PZ"), 10 parts of MEK, and 10 parts of toluene, and dispersing the mixture uniformly using a high-speed rotating mixer. ELM-100H: [ka]

[0147] A polyethylene terephthalate film with a release layer ("AL5" manufactured by Lintec Corporation, thickness 38 μm) was prepared as a support. The resin varnish was uniformly applied onto the release layer of this support so that the thickness of the resin composition layer after drying was 40 μm. The resin varnish was then dried at 80°C to 100°C (average 90°C) for 4 minutes to obtain a resin sheet including a support and a resin composition layer.

[0148] [Example 2] In Example 1, 1) Biphenyl-based epoxy resin ("NC-3100" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent: 258 g / eq.) was not used in the experiment. 2) The amount of naphthalene-based epoxy resin (DIC "HP-4032-SS", epoxy equivalent 144g / eq.) was changed from 6 parts to 8 parts. 3) The amount of naphthalene-based epoxy resin ("ESN-4100VEK75" manufactured by Nippon Steel Chemical & Material Co., Ltd., epoxy equivalent 360 g / eq., MEK solution with non-volatile content of 75%) was changed from 8 parts to 9.3 parts. A resin varnish and a resin sheet were prepared in the same manner as in Example 1 except for the above.

[0149] [Example 3] In Example 1, 1) The amount of epoxy resin (Sumitomo Chemical Co., Ltd., "ELM-100H", epoxy equivalent 104g / eq.) was changed from 3 parts to 6 parts. 2) The amount of naphthalene-based epoxy resin (DIC "HP-4032-SS", epoxy equivalent 144g / eq.) was changed from 6 parts to 4 parts. 3) The amount of naphthalene-based epoxy resin ("ESN-4100VEK75" manufactured by Nippon Steel Chemical & Material Co., Ltd., epoxy equivalent 360g / eq., MEK solution with non-volatile content of 75%) was changed from 8 parts to 5.3 parts. 4) The amount of active ester curing agent (DIC Corporation's "HPC-8150-62T", toluene solution with 62% nonvolatile content by mass, active ester group equivalent of 234 g / eq.) was changed from 41.9 parts to 43.5 parts. A resin varnish and a resin sheet were prepared in the same manner as in Example 1 except for the above.

[0150] [Example 4] In Example 1, 1) The amount of epoxy resin (Sumitomo Chemical Co., Ltd., "ELM-100H", epoxy equivalent 104g / eq.) was changed from 3 parts to 6 parts. 2) The amount of naphthalene-based epoxy resin (DIC "HP-4032-SS", epoxy equivalent 144g / eq.) was changed from 6 parts to 7 parts. 3) Without using 8 parts of naphthalene-based epoxy resin ("ESN-4100VEK75" manufactured by Nippon Steel Chemical & Material Co., Ltd., epoxy equivalent 360g / eq., MEK solution with non-volatile content of 75%), 4) The amount of active ester curing agent (DIC Corporation's "HPC-8150-62T", toluene solution with 62% nonvolatile content by mass, active ester group equivalent of 234 g / eq.) was changed from 41.9 parts to 45.2 parts. A resin varnish and a resin sheet were prepared in the same manner as in Example 1 except for the above.

[0151] [Example 5] In Example 1, 1) The amount of epoxy resin (Sumitomo Chemical Co., Ltd., "ELM-100H", epoxy equivalent 104g / eq.) was changed from 3 parts to 6 parts. 2) The amount of naphthalene-based epoxy resin (DIC "HP-4032-SS", epoxy equivalent 144g / eq.) was changed from 6 parts to 7 parts. 3) No naphthalene-based epoxy resin ("ESN-4100VEK75" manufactured by Nippon Steel Chemical & Material Co., Ltd., epoxy equivalent 360g / eq., MEK solution with non-volatile content of 75%) was used in the same manner as above. 4) 4 parts of a cresol novolac type hardener (DIC Corporation, "LA-3018-50P", hydroxyl equivalent 151, 2-methoxypropanol solution with non-volatile content of 50%) was added. A resin varnish and a resin sheet were prepared in the same manner as in Example 1 except for the above.

[0152] [Example 6] In Example 5, 4 parts of a cresol novolac type curing agent (DIC Corporation, "LA-3018-50P", hydroxyl equivalent 151, 2-methoxypropanol solution with non-volatile content of 50%) was changed to 3.3 parts of a phenol novolac type curing agent (DIC Corporation, "LA-1356", MEK solution with hydroxyl equivalent 146 and non-volatile content of 60%). A resin varnish and a resin sheet were prepared in the same manner as in Example 5 except for the above.

[0153] [Comparative Example 1] In Example 1, 1) Without using 3 parts of epoxy resin (manufactured by Sumitomo Chemical Co., Ltd., "ELM-100H", epoxy equivalent 104g / eq.), 2) The amount of biphenyl-based epoxy resin (Nippon Kayaku Co., Ltd. "NC-3100", epoxy equivalent 258g / eq.) was changed from 3 parts to 1 part. 3) The amount of naphthalene-based epoxy resin (DIC "HP-4032-SS", epoxy equivalent 144g / eq.) was changed from 6 parts to 4 parts. 4) The amount of naphthalene-based epoxy resin ("ESN-4100VKE75" manufactured by Nippon Steel Chemical & Material Co., Ltd., epoxy equivalent 360g / eq., MEK solution with non-volatile content of 75%) was changed from 6 parts to 3 parts. 5) Add 2 parts of amine-type epoxy resin (ADEKA "EP3950L", epoxy equivalent 95g / eq.) 6) The amount of active ester curing agent (DIC Corporation's "HPC-8150-62T", toluene solution with 62% nonvolatile content by mass, active ester group equivalent of 234 g / eq.) was changed from 41.9 parts to 32.3 parts. A resin varnish and a resin sheet were prepared in the same manner as in Example 1 except for the above. The structure of EP3950L is shown below. [ka]

[0154] [Comparative Example 2] In Comparative Example 1, 1) No naphthalene-based epoxy resin ("ESN-4100VKE75" manufactured by Nippon Steel Chemical & Material Co., Ltd., epoxy equivalent 360g / eq., MEK solution with non-volatile content of 75%) was used. 2) The amount of amine-type epoxy resin (ADEKA "EP3950L", epoxy equivalent 95 g / eq.) was changed from 2 parts to 5 parts. A resin varnish and a resin sheet were prepared in the same manner as in Comparative Example 1 except for the above.

[0155] [Comparative Example 3] In Comparative Example 2, 5 parts of an amine-type epoxy resin (ADEKA Corporation's "EP3950L", epoxy equivalent 95 g / eq.) was changed to 5 parts of a naphthalene-skeleton epoxy resin (Nippon Steel Chemical & Material Corporation's "ESN-4100VEK75", epoxy equivalent 360 g / eq., MEK solution with non-volatile content of 75%). A resin varnish and a resin sheet were produced in the same manner as in Comparative Example 2, except for the above points.

[0156] [Comparative Example 4] In Example 1, 1) The amount of epoxy resin (Sumitomo Chemical Co., Ltd., "ELM-100H", epoxy equivalent 104g / eq.) was changed from 3 parts to 11 parts. 2) The amount of biphenyl-based epoxy resin ("NC-3100" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent 258g / eq.) was changed from 3 parts to 5 parts. 3) The amount of naphthalene-based epoxy resin (DIC "HP-4032-SS", epoxy equivalent 144g / eq.) was changed from 6 parts to 11 parts. 4) Without using 8 parts of naphthalene-based epoxy resin ("ESN-4100VEK75" manufactured by Nippon Steel Chemical & Material Co., Ltd., epoxy equivalent 360g / eq., MEK solution with non-volatile content of 75%), 5) 41.9 parts of active ester curing agent (DIC "HPC-8150-62T", toluene solution with 62% non-volatile content, active ester group equivalent of 234 g / eq.) was used without using 3. 6) 34 parts of a cresol novolak type hardener (DIC Corporation, "LA-3018-50P", hydroxyl equivalent 151, 2-methoxypropanol solution with non-volatile content of 50%) was added. A resin varnish and a resin sheet were prepared in the same manner as in Example 1 except for the above.

[0157] [Measurement of dielectric tangent] The resin sheets prepared in the examples and comparative examples were heated at 190°C for 90 minutes to thermally cure the resin composition layer. The support was then peeled off to obtain a cured product of the resin composition. The cured product was cut into a test piece having a width of 2 mm and a length of 80 mm. The dielectric loss tangent Df of the test piece was measured at a measurement frequency of 5.8 GHz and a measurement temperature of 23°C by a cavity resonance perturbation method using an Agilent Technologies "HP8362B". Measurements were performed on three test pieces.

[0158] [Measurement of glass transition temperature Tg and thermal expansion coefficient CTE] The cured product obtained above was cut into a length of 20 mm and a width of 6 mm to obtain a cured product for evaluation. A first TMA curve was obtained for this cured product for evaluation using a Rigaku thermomechanical analyzer (TMA) at a temperature rise rate of 5°C / min from 25°C to 250°C using a tensile load method. The same measurement was then performed on the same cured product for evaluation to obtain a second TMA curve. From the second TMA curve obtained, the glass transition temperature Tg (°C) and the thermal expansion coefficient CTE (ppm / °C) were determined.

[0159] [Measurement of plating peel strength] (1) Surface preparation for inner layer circuit boards: A glass cloth-based epoxy resin double-sided copper-clad laminate (copper foil thickness 18 μm, board thickness 0.4 mm, Panasonic "R1515A") with inner layer circuits (copper foil) on both sides was prepared as an inner layer circuit board. Both sides of this inner layer circuit board were etched by 1 μm using MEC's ​​"CZ8101" to roughen the copper surface.

[0160] (2) Lamination of resin sheet: The resin sheet was laminated on both sides of the inner layer circuit board using a batch type vacuum pressure laminator (Nikko Materials Co., Ltd., 2-stage build-up laminator, CVP700). This lamination was performed so that the resin composition layer of the resin sheet was in contact with the inner layer circuit board. This lamination was also performed by reducing the pressure for 30 seconds to 13 hPa or less, and pressing at 130°C and a pressure of 0.74 MPa for 45 seconds. Next, a heat press was performed at 120°C and a pressure of 0.5 MPa for 75 seconds.

[0161] (3) Curing of the resin composition: The laminated resin sheet and the inner layer circuit board were heated at 130° C. for 30 minutes, and then heated at 170° C. for 30 minutes to harden the resin composition layer and form an insulating layer. The support was then peeled off to obtain a laminated substrate having an insulating layer, an inner layer circuit board, and an insulating layer in this order.

[0162] (4) Roughening treatment: The laminated substrate was immersed in a swelling solution (Atotech Japan's Swelling Dip Securigant P (aqueous solution of glycol ethers and sodium hydroxide) containing diethylene glycol monobutyl ether). The laminated substrate was then immersed in a roughening solution (Atotech Japan's Concentrate Compact P (aqueous solution of KMnO4: 60 g / L and NaOH: 40 g / L)) at 80°C for 20 minutes. The laminated substrate was then immersed in a neutralizing solution (Atotech Japan's Reduction Shalusin Securigant P (aqueous solution of sulfuric acid)) at 40°C for 5 minutes. The laminated substrate was then dried at 80°C for 30 minutes to obtain "Evaluation Substrate A."

[0163] (5) Semi-additive plating: Evaluation substrate A was immersed in an electroless plating solution containing PdCl2 at 40°C for 5 minutes, and then immersed in an electroless copper plating solution at 25°C for 20 minutes. It was then heated at 150°C for 30 minutes and annealed. An etching resist was then formed, and a pattern was formed by etching. Copper sulfate electrolytic plating was then performed to form a conductor layer with a thickness of 20 μm. An annealing process was then performed at 190°C for 60 minutes to obtain "evaluation substrate B."

[0164] (6) Measurement of plating peel strength: A cut was made in the conductor layer of evaluation board B, surrounding a rectangular portion 10 mm wide and 100 mm long. One end of the rectangular portion was peeled off and held with a gripper (Autocom type testing machine "AC-50C-SL" manufactured by TSE Corporation). The rectangular portion was peeled off vertically with the gripper at room temperature at a speed of 50 mm / min, and the load (kgf / cm) when 35 mm had been peeled off was measured as the plating peel strength.

[0165] [Evaluation of cracks after desmear] A polyethylene terephthalate film with a release layer ("AL5" manufactured by Lintec Corporation, thickness 38 μm) was prepared as a support. The resin varnish was uniformly applied onto the release layer of this support so that the thickness of the resin composition layer after drying was 25 μm. The resin varnish was then dried at 80°C to 100°C (average 90°C) for 2.5 minutes to obtain a resin sheet including a support and a resin composition layer.

[0166] The 25 μm thick resin sheet obtained above was laminated on both sides of a core material (Hitachi Chemical Co., Ltd. "E705GR", thickness 400 μm) in which circular copper pads (copper thickness 35 μm) with a diameter of 350 μm were formed in a grid pattern at intervals of 400 μm so that the residual copper ratio was 60%. Using a batch-type vacuum pressure laminator (Nikko Materials Co., Ltd. 2-stage build-up laminator "CVP700"), the resin composition layer was bonded to the inner layer substrate. This lamination was performed by decompressing for 30 seconds to an atmospheric pressure of 13 hPa or less, and then pressing at a temperature of 100 ° C and a pressure of 0.74 MPa for 30 seconds. This was placed in a 130 ° C oven and heated for 30 minutes, and then transferred to a 170 ° C oven and heated for 30 minutes. The support layer was then peeled off, and the resulting circuit board was immersed in a swelling solution, Swelling Dip Securigant P, manufactured by Atotech Japan Co., Ltd., for 10 minutes at 60°C. Next, the circuit board was immersed in a roughening solution, Concentrate Compact P, manufactured by Atotech Japan Co., Ltd. (aqueous solution of KMnO4: 60g / L, NaOH: 40g / L), for 30 minutes at 80°C. Finally, the circuit board was roughened by immersing the circuit board in a neutralizing solution, Reduction Solution Securigant P, manufactured by Atotech Japan Co., Ltd., for 5 minutes at 40°C. After the roughening treatment, 100 copper pads of the circuit board were observed, and the presence or absence of cracks in the insulating layer was evaluated according to the following criteria. Good: 10 or fewer cracks. ×: More than 10 cracks.

[0167] [Table 1]

[0168] In Examples 1 to 6, it was confirmed that even when components (C) to (H) were not contained, the same results as those in the above Examples were obtained, although to a different extent.

Claims

1. (A) an epoxy resin represented by the following general formula (1), and (B) an active ester-based curing agent; The component (B) contains a naphthalene-type active ester curing agent containing a naphthalene structure, A resin composition, wherein the content of component (B) is 5% by mass or more and 30% by mass or less, when the total amount of non-volatile components in the resin composition is 100% by mass. 【Chemistry 1】 (In general formula (1), R represents an alkyl group.)

2. The resin composition according to claim 1 , further comprising (C) an inorganic filler.

3. The resin composition according to claim 1 or 2, further comprising (D) an elastomer.

4. The resin composition according to any one of claims 1 to 3, further comprising (E) a high molecular weight component.

5. The resin composition according to any one of claims 1 to 4, further comprising (F) a curing accelerator.

6. The resin composition according to any one of claims 1 to 5, wherein the component (A) comprises an epoxy resin represented by general formula (2). 【Chemistry 2】 (In general formula (2), R 1 represents an alkyl group.)

7. A resin sheet comprising a support and a resin composition layer provided on the support, the resin composition layer comprising the resin composition according to any one of claims 1 to 6.

8. A printed wiring board comprising an insulating layer formed from a cured product of the resin composition according to any one of claims 1 to 6.

9. A semiconductor device comprising the printed wiring board according to claim 8.

Citation Information

Patent Citations

  • One-pack epoxy rein composition

    JP1991139517A

  • Resin composition

    JP2019014843A

  • Resin composition

    JP2019019231A

  • Photosensitive resin composition, photosensitive element, and printed wiring board and method for manufacturing the same

    JP2019066792A

  • Resin composition, sheet-like laminated material, printed wiring board, and semiconductor device

    JP2019210319A